Interferensi Leksikal Bahasa Inggris Dalam Komunitas Ojek Daring Surabaya - Lista tun Khasanah; Surana surana (JOB (Jurnal Online Baradha), 2021)
Abstract Collection of other language elements will provide the advantage that it can enrich the language in question. The language of the recipient will be harmed if the entry of other languages ​​has the impact of confounding the structure so that in its use there are rules deviations or cause interference symptoms. The research method in this research is a descriptive method by taking data from the Ojek Online Community. Data analysis refers to solving problems that are qualitative in nature with a distributional approach. The results of this study are first, the form of lexical interference in foreign languages ​​in Javanese, the spoken variety includes basic word forms, compound words, rephrases and affix words. Second, the meaning of English lexical interference in spoken Javanese, namely stating a comparison, stating affirmation, stating a situation, stating a place, stating a destination, stating properties, stating an action, stating a tool and functioning as a pointer. Third, the factors that cause lexical interference of English to the use of spoken Indonesian, namely there are two factors. Internal factors, among others, 1) the habits of speakers using programming languages, 2) limitations of speakers using spoken Javanese language. While external factors include 1) the habit of using English which refers to the online motorcycle taxi application, 2) the habit of using language in the Surabaya online motorcycle taxi community, and 3) the lack of mastery of vocabulary in Javanese. Keywords: Interference, lexical interference, online motorcycle taxis Abstrak Pemungutan unsur bahasa lain akan memberi keuntungan yaitu dapat memperkaya khasanah bahasa yang bersangkutan. Bahasa penerima akan dirugikan apabila masuknya bahasa lain berdampak mengacaukan struktur sehingga dalam pemakaiannya terjadi penyimpangan kaidah atau menimbulkan gejala interferensi. Metode penelitian dalam penelitian ini adalah metode deskriptif dengan mengambil data dari Komunitas Ojek Daring. Analisis data mengacu pada pemecahan masalah yang bersifat kualitatif dengan pendekatan bersifat distribusional. Hasil penelitian ini adalah Pertama bentuk interferensi leksikal bahasa asing pada bahasa Jawa ragam lisan meliputi bentuk kata dasar, kata majemuk, kata ulang dan kata berimbuhan. Kedua, makna interferensi leksikal bahasa Inggris pada bahasa Jawa ragam lisan, yaitu menyatakan perbandingan, menyatakan penegasan, menyatakan keadaan, menyatakan tempat, menyatakan tujuan, menyatakan sifat, menyatakan tindakan, menyatakan alat dan berfungsi sebagai penunjuk. Ketiga, faktor yang menyebabkan interferensi leksikal bahasa Inggris pada penggunaan bahasa Jawa ragam lisan, yaitu terdapat dua faktor. Faktor internal antara lain, 1) kebiasaan penutur menggunakan bahasa pemrograman, 2) keterbatasan penutur menggunakan bahasa Jawa lisan. Sedangkan faktor eksternal antara lain 1) kebiasaan penggunaan bahasa Inggris yang mengacu pada aplikasi ojek daring tersebut, 2) kebiasaan penggunaan bahasa di lingkungan komunitas ojek daring Surabaya, dan 3) kurangnya penguasaan kosa-kata dalam bahasa Jawa. Kata Kunci : Interferensi, Interferensi leksikal, Ojek daring